Analisis Keterampilan Proses Sains Mahasiswa PGMI pada Materi Sifat-Sifat Cahaya - Trisnawati, Oky Ristya (Paedagogie, 2025)
Learning Natural Sciences is considered to be a difficult problem for students so students' science process skills are less than optimal. This study aims to explore the science process skills of students of Elementary Madrasah Teacher Education, Institut Agama Islam Nahdlatul Ulama Kebumen in the course of basic concepts of Natural Sciences, especially the material on the properties of light. This study is a descriptive qualitative study. This study was taken from students of Elementary Madrasah Teacher Education Semester IV at the Institut Agama Islam Nahdlatul Ulama Kebumen. The number of respondents in this study was 16 students. Data were obtained from observations, in-depth interviews, and documentation. Data were validated using the triangulation method technique. The data were analyzed using an interactive analysis process, including data reduction, data presentation, and verification/conclusion. The results of the study showed that students of the Elementary Madrasah Teacher Education Institut Agama Islam Nahdlatul Ulama Kebumen had science process skills with a percentage level of 88.10% or excellent, which was indicated by having indicators of the ability to observe, group, clarify, predict, ask questions, conduct experiments, and communicate. The indicator that students most mastered was communicating with a percentage of 95.75%, while the indicator that students less mastered was asking questions with a rate of 75%. These results were caused by students being accustomed to doing percentages and having previous practical experience, but they were only able to ask questions with the practical content of practical activities. Overall, all students of the Elementary Madrasah Teacher Education met the science process skills indicators very well.